Model Rekomendasi Makanan Menggunakan Content-Based dan Collaborative Filtering - Falahah, Falahah; Komalasari, Rita (Ikatan Ahli Informatika Indonesia, 2024)
The Food Recommendation System is one of the most popular implementations of the recommendation system in everyday life.